STUDY THE UNIQUE SOLVABILITY OF BOUNDARY VALUE PROBLEM OF FRANKL FOR MIXED-TYPE EQUATION DEGENERATE ON THE BOUNDARY AND WITHIN THE REGION - N.K. Ochilova (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2014)
In this paper, the existence and the uniqueness of solution of the Frankl type boundary value problem for degenerating equation of the mixed type are proved.